Study and Simulation Stability of the Vehicle Body with the Air Suspension - Ho Xuan Truong; Lanh Le Thanh; Thoi Le Nam (International Journal of Research in Vocational Studies (IJRVOCAS), 2022)
The article mentions to the content of the study simulation stability trunk with air suspension uses Matlab Simulink software, the study effects of air suspension system to stability trunk when the vehicle is moving. Since we conduct simulated stability truck control with air suspension based on parameters Mobihome HB120SSL Thaco bus. Results thesis has successfully built a simulation model for stability trunk in linear motion on vehicle specifications Thaco Mobihome HB120SSL, survey control changes in these parameters as the stiffness of the air suspension system helps stability trunk when the vehicle moves. The simulation results indicate that, when using the air suspension system can change the parameters of the elastic member stiffness according to the distribution of the load on the wheels, thereby limiting air suspension get the trunk moving at the wheel, greatly improving the stability of the trunk when Thaco Mobihome HB120SSL bus move.